EFFECT OF SEWAGE SLUDGE ON TOMATO (Lycopersicon esculentum L.) - D. JAGDISHWAR REDDY, K. BHAVYA, A. BABY, A. MANOHAR RAO and (The Journal of Research, PJTSAU, 2017)
India is the third largest producer of tomato after China and USA. Tomato is one of the most important vegetable crop from nutritional as well as consumption point of view. It tops the list of canned vegetables. In India, Andhra Pradesh leads in tomato production with an area of 95,000 hectares and an annual production of 19.14 lakh Mt.